Applying the Rule of Social Mobility in Identifying Policy Frameworks to Attract High-Quality Science and Technology Human Resources to Universities - Anh, Nguyen Thi Quynh (VNU Journal of Science: Policy and Management Studies, 2021)
The fourth industrial revolution has created a great boost in the development of technology, prompting countries to seek intelligent management solutions in all fields. This also brings opportunities and challenges in attracting and using high-quality human resources for organizations and countries in current global competition. According to Klaus Schwab, who introduced the term Fourth Industrial Revolution, talent, rather than capital, will represent the factor of production. This is both an opportunity and a challenge for organizations and countries in the competition for high-quality scientific and technological human resources. Universities are also on this trend. The article will analyze the need to apply the rule of social mobility in policy identification to attract high-quality science and technology human resources to universities. These research contents initially contribute to providing the arguments for the process of making policies to attract talents or high-quality scientific and technological human resources in universities in the context of the fourth industrial revolution. Keywords: Social mobility, the Fourth industrial revolution, policies to attract high-quality science and technology human resources. References [1] K. Swab, The Fourth Industrial Revolution, 2016, pp. 37-48. [2] D.V. Cuong, T.L. Kien, From brain drain to brain circulation: Some theoretical issues and policy implications to attract highly qualified scientists to return to Vietnam (in Vietnamese), https://sokhcn.vinhphuc.gov.vn/noidung/tintuc/Lists/KhoaHocCongNghe/View_Detail.aspx?ItemID=1170, 2015 (accessed on 20 February 2021). [3] T.L. Friedman, The world is flat, Publisher: Farrar, Straus and Giroux, 2005. [4] Kazakh University of Economics, Finance and International Trade. What is Academic Mobility? https://kuef.kz/en/cooperation/mobility/, (accessed on 20 February 2021). [5] OECD, Workshop proceedings: Funding for public research in higher education institutions 2010, p. 9 (in Vietnamese). [6] Ministry of Education and Training, Higher education statistics for the school year 2017-2018 (in Vietnamese), https://moet.gov.vn/thong-ke/Pages/thong-ko-giao-duc-dai-hoc.aspx?ItemID=5877, 2019 (accessed on 20 February 2021). [7] N.V. Ty, Innovation of higher education in the context of the Industrial Revolution 4.0 (in Vietnamese). http://tuyengiao.vn/nghien-cuu/ly-luan/doi-moi-giao-duc-dai-hoc-trong-boi-canh-cach-mang-cong-nghiep-4-0-123652, 2019, (accessed on 20 February 2021). [8] T. Linh, The model of smart university model in the 4.0 era (in Vietnamese). https://giaoduc.net.vn/tin-hiep-hoi/mo-hinh-dai-hoc-thong-minh-trong-thoi-dai-40-post185981.gd, 2018, (accessed on 20 February 2021).